2013
DOI: 10.1002/tect.20033
|View full text |Cite
|
Sign up to set email alerts
|

Zircon and apatite thermochronology of the Nankai Trough accretionary prism and trench, Japan: Sediment transport in an active and collisional margin setting

Abstract: The Nankai accretionary complex is the most recent addition to the accretionary complexes of southwest Japan and has preserved a record of sediment flux to the trench during its construction. In this study, we use U‐Pb zircon and fission track analysis of both zircons and apatites from sediments taken from the forearc and trench of the Nankai Trough, as well as rivers from southwest Japan to examine the exhumation history of the margin since the Middle Miocene. Modern rivers show a flux dominated by erosion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 83 publications
8
71
1
Order By: Relevance
“…This approach assumes limited compositional variation of source areas and no significant changes in on-land erosional and transport processes in the past 2.5 Ma. This assumption is in good agreement with broadly constant exhumation rates across the studied area and magmatic quiescence in SW Honshu during this period (Kimura et al, 2005;Clift et al, 2013).…”
Section: Composition and Provenance Of Detrital Pyroxenes At Drill Sitessupporting
confidence: 73%
See 2 more Smart Citations
“…This approach assumes limited compositional variation of source areas and no significant changes in on-land erosional and transport processes in the past 2.5 Ma. This assumption is in good agreement with broadly constant exhumation rates across the studied area and magmatic quiescence in SW Honshu during this period (Kimura et al, 2005;Clift et al, 2013).…”
Section: Composition and Provenance Of Detrital Pyroxenes At Drill Sitessupporting
confidence: 73%
“…In contrast, approaches using single grain geochemical analysis or single grain geochronology are not affected by alteration, hydrodynamic and diagenetic effects and, thus, allow a more robust and detailed characterisation of provenance (von Eynatten and Dunkl, 2012). In the Nankai margin, geochronology of detrital zircons can be used to determine the relative contribution of the Inner, Outer and Collision Zones in turbidites (Clift et al, 2013). This approach notably allowed assessment of clastic flux to the Nankai Trough in SW Japan over the past 14 m.y.…”
Section: Sediment Provenance Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…4, p. 204. Such aligned plots have been already adopted by fission track dating groups (e.g., Clift et al 2013). However, a comprehensive view on both, standard error and data distribution characteristics requires further steps.…”
Section: Philosophy and Constructionmentioning
confidence: 99%
“…There have been significant fluctuations of sediment provenance and shifts in delivery pathways and rerouting since the basin's initiation [35][36][37][38]. A margin-wide assessment has shown that the submarine fans have transformed over time from a braided channel-dominated system to a small fan dominated system with shrinking, separated, small basins; to a trough fill turbidite system; to a channel-levee system [39][40][41].…”
Section: Kumano Basin Evolutionmentioning
confidence: 99%